Bismuth-Antimony mixed double perovskites Cs2AgBi1-xSbxBr6 in solar cells. (2019) - Pantaler, Martina; Olthof, Selina; Meerholz, Klaus; Lupascu, Doru C.
Abstract: Reported conversion efficiencies of lead based perovskite solar cells keep increasing steadily. But next to the demand for high efficiency, the need for analogue non-toxic material systems remains. One promising lead free absorber material is the double perovskite Cs2 AgBiBr6 . Interest in this and other double perovskites has been increasing in the last three years and several solar cells using different device structures have been reported. However, the efficiency of these solar cells is merely in the range of 2%. To further improve solar cell performance we prepared mixed bismuth-antimony double perovskite Cs2 AgBi1-x Sbx Br6 where different fractions of antimony (x=0.125, 0.25, 0.375, 0.50) are used. This was motivated by reports of lower bandgap values in these mixed system. After the optimization of preparation of these thin films, we have carefully analysed the effects on the structure, composition, electronic structure, as well as optical properties. Finally, we have fabricated Bi-Sb mixed double perovskite solar cells in a mesoscopic device architecture.